Digital transformation and corporate ESG performance: Research based on a capability-motivation dual framework - Cuicui Huang (PLoS ONE, 2025)
This study systematically examines the impact mechanism and heterogeneous characteristics of digital transformation (DT) on corporate environmental, social, and governance (ESG) performance, using panel data from Chinese A-share listed companies from 2010–2022. The research constructs a “capability-motivation” analytical framework based on resource dependence theory and agency theory, yielding the following conclusions. First, DT has a significant positive effect on corporate ESG performance, which is robustly verified through instrumental variables method and system GMM, among others. Second, DT enhances corporate ESG performance through the dual pathways of alleviating financing constraints (resource effect) and reducing agency costs (governance effect). Third, this promotional effect varies significantly across different lifecycle stages, being more prominent in mature and declining companies but not significant in growth-stage companies. Finally, the positive impact of DT on ESG performance is stronger in state-owned enterprises than in non-state-owned enterprises. This study integrates scattered findings in existing literature through a “capability-motivation” dual framework, providing a more systematic explanation for understanding the relationship between DT and ESG, and offering theoretical foundations and practical implications for companies to formulate differentiated digital-ESG strategies.